Comparing outcomes of ILD patients managed in specialised versus non-specialised centres - Marijic, Pavo; Schwarzkopf, Larissa; Maier, Werner Albert; Trudzinski, Franziska; Kreuter, Michael; Schwettmann, Lars (Respiratory research, 2022)
Early appropriate diagnosis and treatment of interstitial lung diseases (ILD) is crucial to slow disease progression and improve survival. Yet it is unknown whether initial management in an expert centre is associated with improved outcomes. Therefore, we assessed mortality, hospitalisations and health care costs of ILD patients initially diagnosed and managed in specialised ILD centres versus non-specialised centres and explored differences in pharmaceutical treatment patterns.
Gesehen am 15.09.2022